Nanobodies against Pfs230 block Plasmodium falciparum transmission. Issue 24 (22nd December 2022) - Dietrich, Melanie H.; Gabriela, Mikha; Reaksudsan, Kitsanapong; Dixon, Matthew W. A.; Chan, Li-Jin; Adair, Amy; Trickey, Stephanie; O'Neill, Matthew T.; Tan, Li Lynn; Lopaticki, Sash; Healer, Julie; Keremane, Sravya; et al.
Abstract : Transmission blocking interventions can stop malaria parasite transmission from mosquito to human by inhibiting parasite infection in mosquitos. One of the most advanced candidates for a malaria transmission blocking vaccine is Pfs230. Pfs230 is the largest member of the 6-cysteine protein family with 14 consecutive 6-cysteine domains and is expressed on the surface of gametocytes and gametes. Here, we present the crystal structure of the first two 6-cysteine domains of Pfs230. We identified high affinity Pfs230-specific nanobodies that recognized gametocytes and bind to distinct sites on Pfs230, which were isolated from immunized alpacas. Using two non-overlapping Pfs230 nanobodies, we show that these nanobodies significantly blocked P. falciparum transmission and reduced the formation of exflagellation centers. Crystal structures of the transmission blocking nanobodies with the first 6-cysteine domain of Pfs230 confirm that they bind to different epitopes. In addition, these nanobodies bind to Pfs230 in the absence of the prodomain, in contrast with the binding of known Pfs230 transmission blocking antibodies. These results provide additional structural insight into Pfs230 domains and elucidate a mechanism of action of transmission blocking Pfs230 nanobodies.